2021
DOI: 10.3389/fnmol.2021.685143
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNAs in Neurodegenerative Diseases: Pathogenesis and Potential Implications as Clinical Biomarkers

Abstract: Neurodegenerative diseases (NDDs), including Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), and amyotrophic lateral sclerosis (ALS), are progressive and ultimately fatal. NDD onset is influenced by several factors including heredity and environmental cues. Long noncoding RNAs (lncRNAs) are a class of noncoding RNA molecules with: (i) lengths greater than 200 nucleotides, (ii) diverse biological functions, and (iii) highly conserved structures. They directly interact with molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 127 publications
(155 reference statements)
0
24
0
Order By: Relevance
“…Additionally, another RNA-seq study in ALS also described lncRNA dysregulation, and similar implications in PD, further indicating lncRNA utility in AD and other neurodegenerative diseases [ 119 , 120 ]. LncRNAs have also been described in brain tissues as well as specific cell types in AD, further indicating their potential role as a nucleic acid in liquid biopsies in AD (Reviewed in [ 121 , 122 ]). Finally, lncRNAs are also detectable in plasma- and CSF-derived EVs, however, studies are insufficient and require further investigation (Reviewed in [ 123 ]).…”
Section: Main Textmentioning
confidence: 99%
“…Additionally, another RNA-seq study in ALS also described lncRNA dysregulation, and similar implications in PD, further indicating lncRNA utility in AD and other neurodegenerative diseases [ 119 , 120 ]. LncRNAs have also been described in brain tissues as well as specific cell types in AD, further indicating their potential role as a nucleic acid in liquid biopsies in AD (Reviewed in [ 121 , 122 ]). Finally, lncRNAs are also detectable in plasma- and CSF-derived EVs, however, studies are insufficient and require further investigation (Reviewed in [ 123 ]).…”
Section: Main Textmentioning
confidence: 99%
“…Recently, it was discovered that NEAT1 levels were significantly upregulated in the peripheral blood cells of PD patient ( Boros et al, 2020 ). Amyotrophic Lateral Sclerosis (ALS) is prevalent form of motor neuron disease, Data have shown that NEAT1_2 was minimally expressed in the motor neurons of healthy people but highly expressed in the motor neurons of people with early-stage ALS, thus suggesting its utility as a biomarker for early ALS diagnostics ( Zhang M. et al, 2021 ). LncRNAs are particularly attractive biomarkers because they are stable in the blood and other biofluids, and can be readily detected in easily-obtained biofluid samples.…”
Section: Long Non-coding Rnasmentioning
confidence: 99%
“…Additionally, another RNA-seq study in ALS also described lncRNA dysregulation, and similar implications in PD, further indicating lncRNA utility in AD and other neurodegenerative diseases 119,120 . LncRNAs have also been described in brain tissues as well as specific cell types in AD, further indicating its potential role as a nucleic acid in liquid biopsies in AD (Reviewed in 121,122 ). Finally, lncRNAs are also detectable in plasma-and CSF-derived EVs, however studies are insufficient and require further investigation (Reviewed in 123 ).…”
Section: Lncrnasmentioning
confidence: 99%